Medical schools in India: pattern of establishment and impact on public health - a Geographic Information System (GIS) based exploratory study - Yogesh Sabde; Vishal Diwan; Vijay K. Mahadik; Vivek Parashar; Himanshu Negandhi; Tanwi Trushna; Sanjay Zodpey (BMC, 2020)
Abstract Background Indian medical education system is on the brink of a massive reform. The government of India has recently passed the National Medical Commission Bill (NMC Bill). It seeks to eliminate the existing shortage and maldistribution of health professionals in India. It also encourages establishment of medical schools in underserved areas. Hence this study explores the geographic distribution of medical schools in India to identify such under and over served areas. Special emphasis has been given to the mapping of new medical schools opened in the last decade to identify the ongoing pattern of expansion of medical education sector in India. Methods All medical schools retrieved from the online database of Medical Council of India were plotted on the map of India using geographic information system. Their pattern of establishment was identified. Medical school density was calculated to analyse the effect of medical school distribution on health care indicators. Results Presence of medical schools had a positive influence on the public health profile. But medical schools were not evenly distributed in the country. The national average medical school density in India amounted to 4.08 per 10 million population. Medical school density of provinces revealed a wide range from 0 (Nagaland, Dadra and Nagar Haveli, Daman and Diu and Lakshadweep) to 72.12 (Puducherry). Medical schools were seen to be clustered in the vicinity of major cities as well as provincial capitals. Distance matrix revealed that the median distance of a new medical school from its nearest old medical school was just 22.81 Km with an IQR of 6.29 to 56.86 Km. Conclusions This study revealed the mal-distribution of medical schools in India. The problem is further compounded by selective opening of new medical schools within the catchment area of already established medical schools. Considering that medical schools showed a positive influence on public health, further research is needed to guide formulation of rules for medical school establishment in India.